HUBUNGAN MOTIVASI TERHADAP HASIL BELAJAR PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN PADA KELAS X MIPA 1 SMA NEGERI 12 PEKANBARU - Andrea Yuspendra; Drs. Ramadi,S.Pd, M.Kes, AIFO '; Ardiah Juita, S.Pd. M.Pd (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem in this research is the result of learning still unsatisfactory because there are many of the students get score below the passing standard that is under 7. The research will be conducted aims to determine how relationship between motivation for learning outcomes of physical education sports and health in the class x MIPA 1 SMA Negeri 12 Pekanbaru. Sampling in this study using total sampling technique. As a sample of this research is the male students in the Class X MIPA 1 SMAN 12 Pekanbaru that totaling 19 students. The instruments used in this research is a questionnaire aims to measure motivation, learning outcomes obtained from subject teachers of physical education sports and health aims to obtain student grades. After that, the data processed with statistical, to examine normality with lilifors test at significant level α0,05. The hypothesis is suspected that there is a significant relationship among motivation on learning outcomes of physical education sports and health in the class X MIPA 1 SMA N 12 Pekanbaru. Based on analysis of Lilifors test produce LCalculated (x) for 0.189 and Ltable 0.195 and LCalculated (y) for 0.142 and Ltable 0.195. It means Lcalculated <Ltable. Then the samples come from a normal distribution of the population. Then From the calculation of correlation between motivation (X) with the learning outcomes penjasorkes (Y) obtained rcalculated = 0.104 while rtable at significance level α = 0:05 is 0.468. It means in this research there was no correlation between motivation (X) with the learning outcomes penjasorkes (Y).Key Words: Motivation, Learning Outcomes.